2017
DOI: 10.1016/j.ynpai.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Do the psychological effects of vagus nerve stimulation partially mediate vagal pain modulation?

Abstract: There is preclinical and clinical evidence that vagus nerve stimulation modulates both pain and mood state. Mechanistic studies show brainstem circuitry involved in pain modulation by vagus nerve stimulation, but little is known about possible indirect descending effects of altered mood state on pain perception. This possibility is important, since previous studies have shown that mood state affects pain, particularly the affective dimension (pain unpleasantness). To date, human studies investigating the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 102 publications
(153 reference statements)
3
18
0
4
Order By: Relevance
“…Recent studies have shown promising effects of non-invasive vagus nerve stimulation (nVNS) in acute and preventive treatment of migraine and cluster headache [1][2][3][4][5] and also in the treatment of other types of pain, eg, fibromyalgia. 6 Consistent with the clinical effects on headache and migraine, VNS has been shown to reduce trigeminal nociception 7,8 and cortical spreading depression. 9 However, the exact mechanism by which VNS modulates nociception and pain perception is only incompletely understood.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recent studies have shown promising effects of non-invasive vagus nerve stimulation (nVNS) in acute and preventive treatment of migraine and cluster headache [1][2][3][4][5] and also in the treatment of other types of pain, eg, fibromyalgia. 6 Consistent with the clinical effects on headache and migraine, VNS has been shown to reduce trigeminal nociception 7,8 and cortical spreading depression. 9 However, the exact mechanism by which VNS modulates nociception and pain perception is only incompletely understood.…”
Section: Introductionmentioning
confidence: 83%
“…Bidirectional effects of VNS on pain intensity (increased by improved attention vs reduced by positive effects on mood) have been forwarded as an alternative explanation for inconsistent results, and it has been recommended that pain unpleasantness and mood are measured in addition to pain intensity to better characterize the effect of VNS. 7 Based on the above considerations, we hypothesized that VNS (1) activates the descending pain inhibition and (2) reduces supraspinal nociception, possibly with a differential effect on pain unpleasantness vs pain intensity ratings.…”
Section: Introductionmentioning
confidence: 99%
“…Transcutaneous vagus nerves stimulation (t‐VNS) can be achieved using an earplug‐like electrode which sits on the cymba conchae of the outer ear and a handheld battery‐powered electrical stimulator. Brain imaging studies in humans, and tract‐tracing studies in animals, have shown that the auricular branch of the vagus nerve projects to the nucleus tractus solitarius in the brainstem which is the primary relay centre for vagal afferents 9 . t‐VNS has been demonstrated to induce similar patterns of cerebral activation to surgically implanted VNS 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Psychologically, pain can be perceived cognitively (as measured by the intensity of aching, burning, or stinging) (Turk and Rudy, 1992) and affectively (as measured by the unpleasantness of those sensations) (Frangos et al, 2017). Attentional modulation of pain preferentially affects perceived pain intensity, whereas the affective modulation of pain (dependent on one’s mood) preferentially modulates the unpleasantness of pain (Villemure et al, 2003; Loggia et al, 2008).…”
Section: Central Mechanism: Vagal Nervementioning
confidence: 99%
“…Pain which is initially associated with the classic sensory “pain connectome” is later associated with brain regions involved in emotion and reward — over time, pain intensity becomes linked less with nociception and more with emotional and psychosocial factors (Hashmi et al, 2013; Ballantyne and Sullivan, 2015). The trending positive effects of VNS on various cognitive and affective processes are a further indication that psychological factors should be considered in studies and treatments investigating vagal pain modulation (Frangos et al, 2017).…”
Section: Central Mechanism: Vagal Nervementioning
confidence: 99%